Covalent functionalization of single-walled carbon nanotubes using meso-tetra(4-aminophenyl) porphyrin and its zinc complex. Issue 10 (3rd October 2022) - Prabhavathi, G.; Anakha, D. R; Yamuna, R.
Abstract: Covalent linking of 5, 10, 15, 20 meso tetra(4-aminophenyl) porphyrin (TAP) and its zinc complex with single-walled carbon nanotubes (SWCNTs) (nanohybrids A and B, respectively) has been reported. Significant decrease in the intensity of D-band and higher frequency shift of G-band of SWCNT-TAP in Raman spectrum reveals the improved graphitic sp 2 hybridization of SWCNT as compared to SWCNT-ZnTAP. This is due to the functionalization of free base porphyrin (electron donating group) in the nanohybrid A . Shifting of carbonyl stretching frequency from 1700 cm −1 to 1680 cm −1 and further appearance of striking bands in the X-ray photoelectron spectroscopy (XPS) and FTIR spectra of nanohybrids A and B confirm the covalent linking of porphyrin chromophores with SWCNTs. XPS reveals that the extent of functionalization of nanohybrid A is more as compared to nanohybrid B . These nanohybrids demonstrate positive solvatochromism. Upon excitation at 450 nm, the nanohybrids A and B reveal ∼76% and 65% fluorescent quenching of emission bands at 686 and 632 nm, respectively. This is due to the energy or electron transfer from porphyrins to SWCNTs.